Development of specific primers for detection of Karnal bunt pathogen of wheat - Thirumalaisamy, P.P.; Singh, D.V.; Aggarwal, Rashmi; Gogoi, Robin; Gupta, Pramod Kumar; Singh, Pradeep Kumar (Indian Phytopathology, 2011)
Karnal bunt (KB) of wheat caused by Tilletia indica has got prime importance as a quarantine disease although its impact is less on yield (0.3-0.5% loss) and the seed quality. Correct identification and detection of T. indica based on morphological features and germination of teliospores is time consuming. To avoid delay in detection and wrong identification of closely related species of T. indica from wheat seed lots, polymerase chain reaction (PCR) based species-specific primers were developed from rDNA-ITS region and 2.3kb mtDNA fragment of the pathogen. Two ITS primers viz., forward ITS KB F (5’ ACGGAGCTCTTCTTCGGA 3’) and reverse ITS KB R (5’ TCGATGATTCCGAAGAAT 3’) could specifically amplify 570bp amplicon of T. indica. Another primer set viz. forward mtDNA KB F (5’ CAATGTTGGCGTGGCGGCGC 3’) and reverse mtDNA KB R (5’ GGCGGACTACCACTCGAGCT 3’) amplified 885bp amplicon of KB pathogen only. Comparative study of both sets of speciesspecific primers (ITS KB F, ITS KB R and mtDNA KB F, mtDNA KB R) revealed that ITS primers had higher sensitivity, uniform amplification with single resolvable band than the mtDNA sequence based primers. The ITS primers could amplify spore DNA of T. indica obtained from 500 or more teliospores whereas mtDNA primers amplified 5000 or more teliospores DNA. This sensitive molecular tool can be most reliably employed by the seed producers and seed quality testers for detection of KB pathogen.